Pemahaman Digital Marketing Menuju Era 5.0 Di Smk Ma'arif 3 Somalangu Kebumen - Sigit Wibawanto (Politeknik Dharma Patria, 2021)
This community service activity aims to process plastic waste into handicrafts with economic value. Participants in this activity were PKK women in two villages, namely Melaya Village and Candikusuma Village. This activity consists of three stages, namely, planning, implementing, and evaluating. The method applied is counseling and plastic waste processing workshops. The results of the evaluation show that the community service activities have been carried out well. The participants were also enthusiastic and actively participated in this activity. This is indicated by the results of the evaluation, which show an increase in public knowledge. The evaluation results also revealed several challenges in processing plastic waste, such as limited knowledge and skills, limited time, no interest in doing this, difficulty in fighting laziness. The implementation of this activity is expected to reduce environmental pollution caused by plastic waste and create creative businesses in handicrafts with economic value